Learning Style Preferences of Undergraduate Pharmacy Students in Niger Delta University (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Students have preferences about how they like to learn, which affects rate of understanding, assimilation and application of knowledge. Learning styles include assimilating (analytic), diverging (imaginative), converging (common sense) and accommodating (dynamic) styles. Visual, auditory, kinesthetic, tactile, group and individual are other learning preference classification. Appreciation of learning styles by trainers would ensure more productive training outcomes. Data on learning style preferences among pharmacy students in Nigeria is limitedObjectives: To identify learning style preferences among pharmacy students in Niger Delta University.Methods: A cross sectional study of learning style preferences of 300 consenting undergraduate pharmacy students was carried out. Data collection instruments were the validated 6-item Kolb’s Learning Style Inventory (LSI) and the Perceptual Learning Style Preference Questionnaire (PLSPQ). Data collected were entered and analyzed using SPSS version 23. Level of significance was set up at p< 0.05.Results: A total of 279 questionnaires were returned, giving a response rate of 93.0%; majority were female (70.3%). Following Kolb's LSI, the dominant learning style was diverging (48.0%), followed by assimilating (27.6%). Using PLSPQ, the major learning style preferences included tactile (35.4%), visual (34.6%) and kinesthetic (33.6%) learning styles. There was a significant association between gender and learning style preference.Conclusion: Majority of pharmacy students in the study were diverging learners. Also, almost similar proportions were visual, kinesthetic and tactile in term of preferences. All learning styles must be taken into consideration in training students.